ANALISIS JEJARING FARMAKOLOGI SENYAWA METABOLIT SEKUNDER DAUN SUNGKAI (Peronema canescens) TERHADAP JALUR NF-κB DAN IL-6 DALAM PERADANGAN KRONIS - Iwan Santoso, Blegoh; Zaini, Muhammad (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
The potential of Peronema canescens (sungkai) leaf as a natural anti-inflammatory agent is increasingly studied due to its abundant secondary metabolites. This study aimed to investigate the interaction of sungkai leaf compounds with inflammation-related targets, especially NF-κB and IL-6, using pharmacological network analysis. Compounds were obtained from databases and literature, then analyzed through SwissTargetPrediction. The targets were visualized using String to identify networks between bioactive compounds and key inflammatory pathways. Results showed that flavonoids and terpenoids in sungkai interact with targets that regulate NF-κB and IL-6 signaling. The network also revealed key nodes such as TNF, IL1B, and MAPK8 as central mediators. These findings indicate that sungkai leaves have potential as a multi-target anti-inflammatory agent through modulation of inflammatory networks. Further validation through in vitro and in vivo studies is recommended.